Entre hermenêutica filosófica e hermenêutica jurídica: do caráter produtivo da compreensão a uma crítica ao argumento intencionalista - Moita, Cristiano de Aguiar Portela (2016)
The problem of understanding has acquired a perspective as much promising as polemic since the developments of the philosophical hermeneutics. The contemporary legal hermeneutics must deal with this school of thought if it wants to depurate its studies concerning the interpretation and the application of texts, specially the juridical ones. One of the several paths that it must follow is the one related to the meaning of texts, not just one possible meaning, but the adequate and the correct one. And that was always afflicted to the jurist, i.e., to identify a secure criterion to the textual interpretation. Until today, enough updated, some theories struggle to develop methods which can guarantee certain objectivity in the interpretation. That is the case of intentionalism and the originalism. But this search for interpretative certainty cannot disregard what lies behind every and single act of understanding, i.e., a preconceptual structure, essentially historic, that can put down some of these theories of meaning. That does not imply a relativistic attitude, but the recognition that the understanding can be non-arbitrary. Thereby, this work aims in establish a specific contribution that philosophical hermeneutics can provide to legal hermeneutics: a description of the understanding phenomenon that can help jurists avoid some arguments, especially those intentionalists and originalists, which are constantly and decisively brought in some legal decisions. This research seeks to demonstrate this contribution through the following way: firstly, it exposes some of the fundamental traces of philosophical hermeneutics; secondly, it analyses the first contact held between this school of thought and the legal hermeneutics in order to defend the possibility of a correct, non-relativistic interpretation; thirdly, it deepens in the relation between philosophical hermeneutics and legal hermeneutics, through the explanation of the productive character of the understanding, something already noticed by some legal theorists but centralized in such peculiar way by Gadamer around the fundamental problem of the application; lastly, after demonstrating some difficulties in contemporary intentionalists theories, it analyses a legal decision that has used similar arguments, contestable by the theses defended in this research.